2001
DOI: 10.1034/j.1600-0706.2001.950309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil decomposer invertebrates (protozoa and earthworms) on an above‐ground phytophagous insect (cereal aphid) mediated through changes in the host plant

Abstract: 2001. Effects of soil decomposer invertebrates (protozoa and earthworms) on an above-ground phytophagous insect (cereal aphid) mediated through changes in the host plant. -Oikos 95: 441-450.We investigated if the activity of soil invertebrates (protozoa and earthworms) affected the performance of barley and if effects propagated higher up the aboveground food chain into herbivores (cereal aphid, Sitobion a6enae). Barley plants were grown individually in microcosms containing defaunated soil and grass residues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…This was probably because (i) growing cereals continued only in favourable areas and (ii) the use of efficient cultivars compensated for decreased fertilization and (iii) residual N that persisted in the soil from years of over-fertilization. Effect of fertilizers also might be compensated by increased activity of soil decomposers that favour cereal plant vigour and aphid performance (Bonkowski et al, 2001). Even so, we suppose that low fertilizer doses were an important factor influencing cereal aphid abundance, although other factors may have contributed.…”
Section: Causes Of Population Trendsmentioning
confidence: 93%
“…This was probably because (i) growing cereals continued only in favourable areas and (ii) the use of efficient cultivars compensated for decreased fertilization and (iii) residual N that persisted in the soil from years of over-fertilization. Effect of fertilizers also might be compensated by increased activity of soil decomposers that favour cereal plant vigour and aphid performance (Bonkowski et al, 2001). Even so, we suppose that low fertilizer doses were an important factor influencing cereal aphid abundance, although other factors may have contributed.…”
Section: Causes Of Population Trendsmentioning
confidence: 93%
“…For instance, the presence of protozoa increased the number of ears (+ 60 %), seeds (24 %) and the individual seed weight (+32 %) of barley plants, and the crop was even more tolerant to aphid herbivores (Bonkowski et al 2001a). More recently, Krome et al (2009a) showed that A. castellanii enhanced the seed production of Arabidopsis thaliana (Brassicaceae) more than 3-and 7-fold compared to treatments with bacteria and sterile grown plants, respectively.…”
Section: Plant Reproduction and Defensementioning
confidence: 97%
“…Soil decomposer animals such as Protozoa, earthworms and Collembola, and litter distribution in soil, have been shown to increase (Scheu et al 1999a;Bonkowski et al 2001;Wurst et al 2004;Haase et al 2008) but also decrease Schütz et al 2008) aphid reproduction. However, in contrast to the general view that herbivore performance correlates with N concentration in the diet, the eVects of soil animals and litter distribution on aphid reproduction and biomass were not correlated with plant tissue N concentration.…”
Section: Aphid Reproduction and Developmentmentioning
confidence: 98%